Antidote For Smoking - Abd Razak, Dzulkifli (1995)
THERE IS NO ONE ANTIDOTE WHICH can be used to neutralise the thousands of toxic chemicals like those found in a cigarette. This is a fact that must be duly recognised by all. However, there is one quality that can help you kick the habit WILLPOWER. Willpower is also a multicomponent concoction that has a multipronged action against cigarette poisons. Each of the components in willpower not only provide an effective antidotal remedy in itself, but together they can combine to provide a foolproof cure. In fact, it has been proven to work time and again if diligently instituted. How it works: W - willingnessto take positive and affirmative actions to quit smoking I - inculcating new smoke free habits L - learning how to cope without using tobacco L - love and live a healthy lifestyle without tobacco P - positive attitude in facing difficulties while attempting to quit O - orienting all efforts towards success in quitting smoking W - well versed with the actions to be taken in order to quit E - exercise and eat a balance meal in the course of quitting R - resolute, not to begin smoking again